Squeezed coherent states of geometric beams - Wang, Zhaoyang (2025)
Quantum-classical analogy refers to the fact that quantum and classical phenomena share a similar mathematical description and exhibit analogous behaviors, which has advanced optical frontiers. In this work, the mechanism of the squeezed state is incorporated into classical structured light, constructing a novel kind of structured light, termed the squeezed geometric beam, that is, the squeezed coherent state of geometric beams, and revealing a novel quantum-classical analogy between the noise of quantum squeezed state and the beam size of squeezed geometric beams, both evolving with the same squeezing parameter. The presented method provides an inspirational extensible framework to reveal more structured light analogies of quantum states. In addition, it is demonstrated in theory and experiment that thanks to the unveiled squeezing mechanism, the squeezed geometric beam as an information carrier can effectively lower the modal crosstalk, thus boosting the communication capacity of spatial mode multiplexing.